A quantitative study of mast cells in Hodgkin's disease. - Crocker, J (1984)
Mast cells were counted in 45 specimens from patients with Hodgkin's disease and in five lymph nodes showing follicular hyperplasia. A consistent finding was that of few mast cells in the lymphocyte depleted and lymphocyte predominant Rye subtypes of Hodgkin's disease and in the mixed cellularity variant; however, mast cells were much more prevalent in nodular sclerosing Hodgkin's disease and in the hyperplastic nodes. The mast cells were selectively stained by means of the astra blue technique.